Cloud forcing of surface energy balance from in situ measurements in diverse mountain glacier environments - Conway, Jonathan P.; Abermann, Jakob; Andreassen, Liss M.; Azam, Mohd Farooq; Cullen, Nicolas J.; Fitzpatrick, Noel; Giesen, Rianne H.; Langley, Kirsty; Macdonell, Shelley; Mölg, Thomas; Radic, Valentina; Reijmer, Carleen H.; et al. (Cryosphere, 2022)
Clouds are an important component of the climate system, yet our understanding of how they directly and indirectly affect glacier melt in different climates is incomplete. Here we analyse high-quality datasets from 16 mountain glaciers in diverse climates around the globe to better understand how relationships between clouds and near-surface meteorology, radiation and surface energy balance vary. The seasonal cycle of cloud frequency varies markedly between mountain glacier sites. During the main melt season at each site, an increase in cloud cover is associated with increased vapour pressure and relative humidity, but relationships to wind speed are site specific. At colder sites (average near-surface air temperature in the melt season <0 degrees C), air temperature generally increases with increasing cloudiness, while for warmer sites (average near-surface air temperature in the melt season >> 0 degrees C), air temperature decreases with increasing cloudiness. At all sites, surface melt is more frequent in cloudy compared to clear-sky conditions. The proportion of melt from temperature-dependent energy fluxes (incoming longwave radiation, turbulent sensible heat and latent heat) also universally increases in cloudy conditions. However, cloud cover does not affect daily total melt in a universal way, with some sites showing increased melt energy during cloudy conditions and others decreased melt energy. The complex association of clouds with melt energy is not amenable to simple relationships due to many interacting physical processes (direct radiative forcing; surface albedo; and co-variance with temperature, humidity and wind) but is most closely related to the effect of clouds on net radiation. These results motivate the use of physics-based surface energy balance models for representing glacier-climate relationships in regional- and global-scale assessments of glacier response to climate change.
CRIS-Team WoS Importer:2022-09-09